Prospective screening increases the detection of potentially curable hepatocellular carcinoma: results in 8900 high‐risk patients. Issue 12 (22nd April 2013) - Izzo, Francesco; Piccirillo, Mauro; Albino, Vittorio; Palaia, Raffaele; Belli, Andrea; Granata, Vincenza; Setola, Sergio; Fusco, Roberta; Petrillo, Antonella; Orlando, Raffaele; Tosone, Grazia; Scordino, Fabrizio; et al.
Abstract: Objectives: Historically, only 10% of patients with hepatocellular carcinoma (HCC) are diagnosed with early‐stage, potentially curable disease. In this study, chronic hepatitis virus‐infected patients were prospectively screened to determine: (i) the proportion of patients diagnosed with potentially curable HCC, and (ii) survival following curative therapy. Methods: The study included 8900 chronic hepatitis virus‐infected patients enrolled in a prospective screening programme, of whom 1335 (15.0%) were infected with hepatitis B virus (HBV), 7120 (80.0%) with hepatitis C virus (HCV), and 445 (5.0%) with both HBV and HCV. Screening was conducted every 6 months and included serum alpha‐fetoprotein (AFP) measurement and ultrasonography. Curative treatments included liver transplantation, resection, radiofrequency ablation and/or ethanol injection. Results: Hepatocellular carcinoma was diagnosed in 765 (8.6%) patients. Of 1602 patients with cirrhosis, 758 (47.3%) developed HCC. Curative treatment was possible in 523 (68.4%) of the 765 HCC patients. Two‐ and 5‐year rates of overall survival in the curative treatment group were 65% and 28%, respectively, compared with 10% and 0% in the advanced disease group ( P < 0.001). Conclusions: Prospective screening of patients at high risk for the development of HCC increases the proportion of patients diagnosed with potentially curable disease. This may result in an increase in the number of longterm survivors. Screening strategies should focus on patients with chronic HBV or HCV infection who have progressed to cirrhosis because more than 40% of these patients will develop HCC.